Mediatization is the driving force behind the transformation of society and culture - Koshkenov Н.Ж.; Sak Қ.Ө. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
Globalization, the destruction of traditions, glocalization, deterritorization, individualization, mediaization become trends in modern society as a social process that transforms culture and communication. In the article, the authors give an introduction to the term «mediatization» and give a understanding of this theory. Mediatization is also viewed as one of the key factors for changing social and cultural traditions in society.